Intra-operative motor function preservation for resection of primary motor cortex meningioma - Tang, Hailiang; Xu, Feng; Lin, Liqing; Zhu, Hongda; Hua, Lingyang; Luan, Shihai; Xie, Qing; Gong, Ye (Translational Cancer Research, 2018)
Background: Resection of meningioma located at primary motor cortex (PMC) is a great challenge to neurosurgeons due to the possibility of motor cortex injury and drainage venous damage during surgery. Here, we presented our experience in resection of PMC meningioma, with the assistance of preoperative multi-model image planning and intraoperative electrophysiological monitor. By these techniques, patients in our study achieved gross tumor resection (GTR) with appropriate motor cortex and drainage venous protection, and the patients recovered well with less neurologic deficits. Methods: Thirty patients of PMC meningioma were selected for the study during January 2014 to December 2015. All the patients were performed head magnetic resonance imaging (MRI), magnetic resonance venography (MRV) and functional MRI scan before surgery, then all the imaging data were transferred to dextroscope workstation for virtual reality (VR) planning, to display the relationship of tumor, drainage venous and motor cortex. During the operation, somatosensory-evoked potentials (SSEP) was firstly used to locate the central sulcus (CS) and define the PMC area. Then the tumors were carefully removed by avoiding damage the cortex and drainage venous. After tumor resection, motor-evoked potentials (MEP) was applied to evaluate the motor function reservation. Results: All the patients received preoperative image planning, and the relationships of tumor, drainage venous and motor cortex were clearly presented. With the application of SSEP monitor, the CS was firstly determined before tumor resection. Twenty-five cases in our study achieved radical resection of Simpson I, and 5 cases were Simpson II resection. After tumor resection, MEP monitor was used to confirm the preservation of motor function. Four patients suffered from moderate muscle strength decrease postoperatively, 10 patients experienced slight muscle strength decrease, while other 16 patients shared normal muscle strength as preoperative status. When discharge, those affected patients were recommended for further movement rehabilitation therapy. Conclusions: Preoperative multi-model image planning and intraoperative electrophysiological monitor are very useful techniques for resection of PMC meningioma. They could help decrease motor cortex damage and protect the drainage venous during surgery, which is much safer and benefit patient for better prognosis.